Efficiency and safety of lamivudine therapy in patients with chronic HBV infection, dialysis or after kidney transplantation - Lapinski, Tadeusz Wojciech (Baishideng Publishing Group Co., Limited, 2005)
AIM: To analyze the effectiveness and safety of lamivudine treatment in patients with chronic HBV infection undergoing hemodialysis or after kidney transplantation, and to study the frequency of tyrosine - methionine - aspartate - aspartate (YMDD) mutation occurrence after lamivudine treatment. METHODS: We analyzed 91 patients with chronic hepatitis B, among whom, 16 patients underwent hemodialysis, 7 patients had kidney transplantation and 68 patients had normal function of kidney. The hemodialysis patients were treated by lamivudine 300 mg/wk. Patients after kidney transplantation and patients with normal function of kidney were treated with lamivudine 100 mg/d. Therapy lasted for 12 mo. HBV-DNA, HBsAg, HBeAg and anti-HBe, and anti-HCV antibodies were assessed in sera of patients. The analysis was performed before and 6 mo after the end of lamivudine treatment. Before, during and after the lamivudine therapy, the number of erythrocytes, leukocytes, platelets and hemoglobin concentration, ALT and AST activity, as well as bilirubin, urea and creatinine concentrations were analyzed in sera from patients. RESULTS: After the 12-mo lamivudine treatment, elimination of HBV - DNA was observed in 56% patients undergoing hemodialysis and in 53% patients with normal kidney function. Only 1 from 7 (14%) kidney-transplanted patients eliminated HBV-DNA. Furthermore, HBeAg elimination was observed in 36% hemodialysis patients, in 51% patients with normal function of kidneys and in 43% kidney-transplanted patients. Among the patients undergoing dialysis, no YMDD mutation was found after 12 mo of therapy, while it was detected in 9 patients (13%) with normal function of kidney and in 2 kidney-transplanted patients (29%, P<0.006). We did not observe significant side effects of lamivudine treatment in studied patients. CONCLUSION: Effectiveness of lamivudine therapy in dialysis patients is comparable with that in patients with normal function of kidney. Lamivudine treatment is well tolerated and safe in patients with renal insufficiency undergoing hemodialysis and kidney-transplantation. However, in the latter group, high incidence of YMDD mutation after lamivudine treatment was observed.